Gemella bacteremia: an unlikely source of an unlikely cul-prit - Li, William; Gambhir, Harvir (International Journal of Medicine, 2017)
Gemella is an anaerobic or microaerophlic gram positive coccus generally an inhabitant of the oral cavity and gastrointestinal flora which has been associated with poor dentition and infectious endocarditis in the past along with seldom cases of meningitis and liver abscess noted in literature. Oftentimes co-existing with other bacteria as a mixed infection, we highlight the case of a bacteremic individual with gemella as a single isolated organism from a source gemella is not commonly known to inhabit.